Response of reindeer mating time to climatic variability - Amélie Paoli; Robert B. Weladji; Øystein Holand; Jouko Kumpula (BMC Ecology, 2020)
Abstract Background The breeding time of many species has changed over the past 2–3 decades in response to climate change. Yet it is a key reproductive trait that affects individual's parturition time and reproductive success, and thereby population dynamics. In order to predict how climate change will affect species’ viability, it is crucial to understand how species base their reproductive efforts on environmental cues. Results By using long-term datasets of mating behaviours and copulation dates recorded since 1996 on a semi-domesticated reindeer population, we showed that mating time occurred earlier in response to weather conditions at different key periods in their annual breeding cycle. The mating time occurred earlier following a reducing snow cover in early spring, colder minimum temperatures in the last 2 weeks of July and less precipitation in August-September. Conclusions The mediated effect of a reduced snow cover in early spring on improving individuals’ pre-rut body weight through a better availability of late winter food and reduced costs of locomotion on snow would explain that mating time has occurred earlier overtime. A lower level of insect harassment caused by colder maximum temperatures in July might have caused an advance in mating time. Less precipitation in August-September also caused the mating time to occur earlier, although the direct effects of the last two weather variables were not mediated through the pre-rut body weight of individuals. As such, the causal effects of weather conditions on seasonal timing of animals are still unclear and other mechanisms than just body weight might be involved (e.g. socio-biological factors). The plastic response of reindeer mating time to climatic variability, despite supplemental feeding occurring in late April, demonstrated that environmental factors may have a greater influence on reproductive outputs than previously thought in reindeer.